A Sliding Mode Force and Position Controller Synthesis for Series Elastic Actuators. Issue 1 (15th April 2019) - Sariyildiz, Emre; Mutlu, Rahim; Yu, Haoyong
Summary: This paper deals with the robust force and position control problems of series elastic actuators (SEAs). It is shown that an SEA's force control problem can be described by a second-order dynamic model which suffers from only matched disturbances. However, the position control dynamics of an SEA is of fourth order and includes matched and mismatched disturbances. In other words, an SEA's position control is more complicated than its force control, particularly when disturbances are considered. A novel robust motion controller is proposed for SEAs by using disturbance observer (DOb) and sliding mode control. When the proposed robust motion controller is implemented, an SEA can precisely track desired trajectories and safely contact with an unknown and dynamic environment. The proposed motion controller does not require precise dynamic models of environments and SEAs. Therefore, it can be applied to many different advanced robotic systems such as compliant humanoids, industrial robots and exoskeletons. The validity of the proposed motion controller is experimentally verified.